Localization and characterization of a gas bubble stream at a Congo deep water seep site using a 3D gridding approach on single-beam echosounder data. (November 2018) - Wenau, S.; Spiess, V.; Keil, H.; Fei, T.
Abstract: This study investigates the geometry and temporal variation of a prominent gas bubble stream from a seafloor pockmark in the Lower Congo Basin. We present results of a 3D gridding approach of singlebeam echosounder water column data (Parasound 18 kHz) that increases the lateral resolution and improves the localization of anomalies beyond the inherent depth-dependent footprint size of the sonar system. This allows a detailed reconstruction of gas bubble trajectories through the water column, revealing a stable gas bubble stream for the deepest 1000 m. The bubbles are shifted laterally by ∼200 m in the transition zone between North Atlantic Deep Water and Antarctic Intermediate Water with a reconstructed current velocity of ∼4 cm/s. The direction of lateral shift varies throughout the ∼15 h survey possibly because of internal waves and small-scale eddies at the water mass boundary. Furthermore, a stacking of SBES water column data acquired during sampling stations showed a periodic variation in seepage intensity with periods of 6 and 8 min, which are likely related to temporally modulated gas supply to the sea floor. Singlebeam echosounder are commonly limited by their small coverage of the survey area during individual passes and their footprint size in detailed imaging of individual seep sites, especially in the deep sea. The presented gridding method for singlebeam echosounder data may facilitate the use of such data in deep water gas bubble stream identification and localization. Highlights: Gas bubbles in the water column are mapped using 3D data grids of single-beam echosounder data. Gas bubbles are shifted laterally in the transition zone between North Atlantic Deep Water and Antarctic Intermediate Water. Lateral shift of gas bubbles should vary due to internal waves or eddies. Seepage intensity is variable and shows periodicities of 6 and 8 minutes.